English Indonesian translation application for Android - Poh, Yong Huat (2015)
The Final Year Project Report summarizes the author’s work in the Final Year Project. As mobile devices are becoming an essential part of many people’s life, mobile application functions have increased in its importance and may go a long way in bringing convenience to daily activities. Communication is an important aspect of everyone’s daily lives. A mobile language translator application will come in handy for many purposes such as in the tourism industry, for communicating with oversea partners for business purpose, and for self-learners. The Eclipse IDE have been used to build the application. The project went go through several steps in its creation such as logical design, layout implementation, speech synthesis integration, Microsoft Translate and Speech Recognition feature. The project was successfully implemented and is available to install on Android devices. The author utilized the Google Speech Recognition to translate the user’s speech into text. The text would then be sent to Microsoft Bing Translator to be translated into text of the desired language. Finally, the translated text will be read using the Text-To-Speech Engine. The objectives of the Translator are met and the author went on to expand the features. More languages were added to make it relevant to a wider population. A total of 38 languages are available for translation. However, there are a few languages which the speech output could not be read out.